Ameliorative effect of lycopene on antioxidant status in Cyprinus carpio during pyrethroid deltamethrin exposure - Yonar, M. Enis; Sakin, Fatih (Academic Press Inc Elsevier Science, 2011)
The aim of the present study was to investigate the ameliorative properties of lycopene against the toxic effects of deltamethrin (DM) by examining oxidative damage markers such as lipid peroxidation and the antioxidant defense system components in carp (Cyprinus carpio). The fish were divided into seven groups of 15 fish each and received the following treatments: Group 1, no treatment; Group 2, orally administered corn oil; Group 3, oral lycopene (10 mg/kg body weight); Group 4, exposure to 0.018 mu g/L DM; Group 5, exposure to 0.018 mu 4/L DM plus oral administration of 10 mg/kg lycopene; Group 6, exposure to 0.036 mu g/L DM; and Group 7, exposure to 0.036 mu g/L. DM plus oral administration of 10 mg/kg lycopene. Treatment was continued for 14 days, and at the end of this period, blood and tissue (liver, kidney, and gill) samples were collected. Levels of malondialdehyde (MDA) and reduced glutathione (GSH) as well as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) activities were determined in blood and tissues for measurement of oxidant-antioxidant status. A significant elevation in the level of MDA, as an index of lipid peroxidation, and reductions in antioxidant enzyme activities (SOD, CAT, and GSH-Px) and low molecular weight antioxidant (GSH) levels were observed in DM-exposed fish. Treatment with lycopene attenuated the DM-induced oxidative stress by significantly decreasing the levels of MDA. In addition, lycopene significantly increased the SOD, CAT, and GSH-Px activities and the level of GSH. The present results suggest that administration of lycopene might alleviate DM-induced oxidative stress. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Pesticides; Deltamethrin; Lycopene; Oxidative stress; Antioxidant enzymes; Fish